Antimicrobial non-porous surfaces: a comparison of the standards ISO 22196:2011 and the recently published ISO 7581:2023 - Maitz, Stephanie; Poelzl, Sabine; Dreisiebner, Daniela; Zarschenas, Eva; Kittinger, Clemens (Frontiers in Microbiology, 2024)
The application of antimicrobial surfaces requires the proof of their effectivity by in vitro methods in laboratories. One of the most well-known test methods is ISO 22196:2011, which represents a simple and inexpensive protocol by applying the bacterial suspension with known volume and concentration covered under a polyethylene film on the surfaces. The incubation is then done under defined humidity conditions for 24 h. Another approach for testing of non-porous surfaces is the newly published ISO 7581:2023. A “dry test” is achieved through spreading and drying 1 µl of a bacterial suspension on the surface. In this study, low alloyed carbon steel, polyethylene terephthalate (PET) and glass specimens were tested uncoated (reference) and coated with zinc according to both ISOs to compare and to evaluate the advantages and disadvantages of each one of them. Although ISO 7581:2023 allows a more realistic test environment than ISO 22196:2011, the reproducibility of the results is not given due to the low application volume. In addition, not all bacterial strains are equally suitable for this testing type. Individual adaptations to the protocols, including incubation conditions (time, temperature or relative humidity), testing strains and volume, seem necessary to generate conditions that simulate the final application. Nevertheless, both ISOs, if used correctly, provide a good basis for estimating the antimicrobial efficacy of non-porous surfaces.